Comparative assessment of morphological, cytological, and photosynthetic characteristics of the induced octoploid and its tetraploid counterpart of Celosia argentea L. - Rohit Bharati; Yamen Homaidan Shmeit; Jana Hanzal Šedivá; Tomáš Thanh Nguyen Cong; Jiban Kumar Kundu; Lucie Severová; Roman Svoboda; Eloy Fernández-Cusimamani (BMC Plant Biology, 2024)
Abstract Background Celosia argentea is a widely recognized plant for its ornamental qualities and therapeutic uses in traditional medicine. As demand for such multipurpose plants grows, enhancing its phenotypic and physiological traits could further expand its commercial potential. Polyploidization, particularly through chemical treatments like oryzalin, offers a method to induce genetic variation and potentially improve desirable traits in plants. Results Tetraploid (2n = 4×= 36) nodal segments of C. argentea were treated with oryzalin under in vitro conditions, resulting in successful induction of octoploidy (2n = 8×= 72). Flow cytometry and chromosome counting confirmed polyploidization, with the highest induction rate achieved using 40 µM oryzalin for 24 h. Comparative analyses between octoploid and tetraploid plants revealed significant differences in morphological traits, including increased stem and leaf thickness, larger leaf area, inflorescence characteristics and more compact growth in the octoploids. Additionally, octoploids exhibited enhanced chlorophyll content and altered photosynthetic characteristics, along with notable changes in stomatal size and density. Ploidy stability was maintained across generations, ensuring the heritability of the induced traits. Conclusions In vitro polyploidization in C. argentea led to significant phenotypic and physiological improvements, demonstrating its potential for application in ornamental horticulture and plant breeding. This research contributes to the understanding of the impact of in vitro polyploidization on plant development, offering insights for the commercial cultivation and enhancement of C. argentea. Clinical trial number Not applicable.